Modele jaźni w samowiedzy - Pacholik-Żuromska, Anita (Filozofia Nauki, 2019)
This article argues for an externalist self-model in self-knowledge, as an answer to the question of how to defend self-knowledge in the face of evident errors in self-cognition such as self-illusions. The externalist model is contrasted with an internalist model, although both are based on a predictive coding mechanism. The main thesis is that for preserving the status of self-knowledge as knowledge an external element is needed — namely, some feedback from the environment — which corrects not only cognitive prediction errors regarding the world but also errors in self-cognition by forcing the proper action of the subject (agent) and dynamic adaptation of the model of the embodied self. The mechanism of self-corrections is best described by externalist models.